Spatial interpolation of soil hydraulic properties and simulated rice yield - Wopereis, M.C.S.; Stein, A.; Kropff, M.J.; Bouma, J. (Wiley, 1996)
. Simulated estimates of crop yield were made for rainfed rice in a 50 ha dryland rice area. The aim was to investigate how soil units and management units of different sizes with different yields could be used to obtain values for areas of land. Two procedures were applied. First, yields were simulated at six sites, that were representative of six soil mapping units. Second, yields were simulated using soil information from 133 auger sites, and were interpolated over management units using block kriging. Differences between the two procedures for the total area and for a test set of 22 additionally sampled locations were small. A 60% increase in precision was achieved when relatively large management units were defined.A Geographical Information System was used to identify areas with greatest yield potential for rainfed dryland rice. Statistical analysis showed that the six soil units could be grouped into three yield classes. The largest yields were obtained for a sub‐area comprising 11% of the survey area which was associated with a slowly permeable Bg horizon in the soil profile.It was concluded that the best procedure for the spatial interpolation of simulated rice yield should be based on preliminary simulation of crop yields. A sensitivity analysis of the impact of weather variability and soil heterogeneity on the variation of yield was useful to detect the importance of their contributions. The procedures developed in this study are of value in obtaining a reliable estimate of average yield, and can consequently be used for associated cost‐benefit calculations.